องค์ประกอบของการบริหารงานกิจการนักเรียนของโรงเรียนร่วมพัฒนา - Lin, Lu Rui; วนิชกุล, จุมพจน์; เผ่าวงศากุล, สาโรจน์ (วารสาร ศึกษาศาสตร์ มมร, 2020)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาและวิเคราะห์องค์ประกอบของการบริหารงานกิจการนักเรียนของโรงเรียนร่วมพัฒนา และเพื่อยืนยันการบริหารงานกิจการนักเรียนของโรงเรียนร่วมพัฒนา กลุ่มตัวอย่างที่ใช้ในการวิจัยครั้งนี้ คือ ผู้อำนวยการสถานศึกษา รองผู้อำนวยการสถานศึกษา หัวหน้าฝ่ายกิจการนักเรียน อาจารย์ที่ปรึกษา และครูผู้สอนของโรงเรียนร่วมพัฒนา จำนวน 210 คน เครื่องมือที่ใช้เป็นแบบสอบถามแบบมาตราส่วนประเมินค่า 5 ระดับ มีค่าความเชื่อมั่นเท่ากับ 0.98 สถิติที่ใช้ในการวิเคราะห์ข้อมูลได้แก่ความถี่ ร้อยละ ค่าเฉลี่ย และส่วนเบี่ยงเบนมาตรฐาน วิเคราะห์องค์ประกอบเชิงสำรวจด้วยการวิเคราะห์ตัวประกอบเชิงสำรวจและการวิเคราะห์   ตัวประกอบเชิงยืนยัน      ผลการวิจัยพบว่า องค์ประกอบของการบริหารงานกิจการนักเรียนของโรงเรียนร่วมพัฒนา พบว่า มีจำนวน 7 องค์ประกอบ จำนวน 57 ตัวแปร และตัวแปรในทุกองค์ประกอบมีค่าน้ำหนักองค์ประกอบอยู่ในระหว่าง     0.503 ถึง 0.784 เรียงตามลำดับ ได้แก่ การส่งเสริมความรู้และทักษะนักเรียน มีตัวแปรจำนวน 17 ตัวแปร      การส่งเสริมสุขภาพอนามัยและนันทนาการของนักเรียน มีตัวแปรจำนวน 11 ตัวแปร ระบบดูแลช่วยเหลือนักเรียน มีตัวแปร จำนวน 6 ตัวแปร การส่งเสริมวินัย คุณธรรม และจริยธรรมของนักเรียน มีตัวแปรจำนวน 6 ตัวแปร    การปกครองนักเรียน มีตัวแปรจำนวน 6 ตัวแปร การส่งเสริมความสามารถในการปฏิบัติงานของนักเรียน มีตัวแปร              จำนวน 5 ตัวแปร การส่งเสริมประชาธิปไตยในโรงเรียน มีตัวแปรจำนวน 6 ตัวแปร                                        องค์ประกอบของการบริหารงานกิจการนักเรียนของโรงเรียนร่วมพัฒนา ประกอบด้วย 7 องค์ประกอบ คือ การส่งเสริมความรู้และทักษะนักเรียน การส่งเสริมสุขภาพอนามัยและนันทนาการของนักเรียน ระบบดูแลช่วยเหลือนักเรียน การส่งเสริมวินัย คุณธรรม และจริยธรรมของนักเรียน การปกครองนักเรียน การส่งเสริมความสามารถในการปฏิบัติงานของนักเรียน การส่งเสริมประชาธิปไตยในโรงเรียน ทั้งนี้ องค์ประกอบมีความสอดคล้องกับข้อมูลเชิงประจักษ์โดยมีค่าดัชนีความกลมกลืนเป็นไปตามเกณฑ์ (=797.73, df=1532, p=1.00, CFI=1.00, GFI=0.98, AGFI=0.97, RMSEA=0.0, SRMR=0.005, RMR=0.011, CN=487.73)     The purpose of this research was to study and analyze the elements of student affairs administration of the partnership schools and to confirm the administration of student affairs of the partnership schools. The sample group used in this research was the director of the educational institution, Deputy Director of Educational Institution, Head of Student Affairs, Advisors And teachers of the partnership schools, total of 210 people. Questionnaires of returned, A 5 – level rating scale questionnaire with reliability of 0.98 was used to collect data which were analyzed in terms of frequency, percentage, mean, and standard deviation. Exploratory Factor Analysis (EFA) was done by factorial extraction, and was analyzed by Confirmatory Factor Analysis (CFA).The research findings:1. The elements of student affairs administration of the partnership schools were found 7 elements, total 57 variables and the component weight value of each component was between 0.503 - 0.784 as written in descending order: There are 17 variables about promotion of knowledge and skills for students, there are 11 variables about promotion of health and recreation for students, there are 6 variables about support system for student , there are 6 variables about promotion discipline, morality and ethics of students, there are 6 variables about student administration, there are 5 variables promoting students' performance ability, There are 6 variables about promoting democracy in schools.2. The elements of student affairs administration of the partnership schools found that there were 7 components: The promotion of knowledge and skills for students, the promotion of health and recreation for students, the support system for student , the promotion discipline, morality and ethics of students, the student administration, the promoting students' performance ability, the promoting democracy in schools. The composition is in harmony with the empirical data. (=797.73, df=1532, p=1.00, CFI=1.00, GFI=0.98, AGFI=0.97, RMSEA=0.0, SRMR=0.005, RMR=0.011, CN=487.73)